A Prospective Study to Compare Clinical and Radiological Outcomes of Functionally versus Mechanically Aligned Knees Following Robotic Total Knee Arthroplasty - Paul, Amal A.; Thilak, Jai (The Journal of Knee Surgery, 2025)
Total knee arthroplasty (TKA) is one of the most effective treatment options for patients with end-stage osteoarthritis of the knee. However, one out of five patients remains unhappy with the outcomes. In recent years, more emphasis has been given to knee alignment approaches as a potential solution. The main objective of this study was to compare the clinical and functional outcomes between patients undergoing robot-assisted TKA using mechanical alignment (MA) or functional alignment (FA). This prospective nonrandomized study enrolled 40 patients (20 patients in each group). The procedure was performed by a single surgeon using FA or MA. In addition to other measures, the New Knee Society Score (NKSS) and Oxford Knee Score (OKS), and modified forgotten joint scores (MFJS) were recorded, and the patients were followed up until 18 months. The baseline characteristics, including age, gender, and body mass index, did not differ statistically between the groups. All parameters of the NKSS, the OKS, and the MFJS were improved at 18 months in the FA-TKA group compared with the MA-TKA group. The pain score and time to straight leg raise were better in the FA-TKA versus the MA-TKA group (p < 0.001). This study suggests that robotic TKA with the FA approach could improve patient satisfaction, along with fulfillment of patients' expectations from the surgery, through 18 months of follow-up compared with the MA approach. Due to the small sample size of this study, future studies are needed to confirm these findings.
Keywords: total knee arthroplasty; robotic-assisted TKA; functional alignment; MAKO